Prevalence of multidrug resistant (MDR) food-borne pathogens in raw chicken meat in Dhaka city, Bangladesh: an increasing food safety concern (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The present study was performed to investigate the prevalence of multidrug resistant (MDR) food-borne pathogens in raw chicken meat in Dhaka city, Bangladesh: an increasing food safety concern. A total of 100 meat samples (05 from each market) were collected from randomly selected 20 retail markets of Dhaka city using sterile polythene bags in a view to prevent extraneous contamination. The collected meat samples were then processed and inoculated onto nutrient broth and nutrient agar plates for isolation. The isolated organisms were identified based on staining, motility, cultural and biochemical properties according to standard laboratory methods. The isolated bacteria were also subjected to characterize their antibiotic sensitivity. In the present study, it was revealed that 100% of samples were contaminated by at least one species of bacteria belonging to 5 genera such as Staphylococcus, Escherichia coli, Salmonella, Enterobacter and Bacillus. Out of total 100 meat samples, 56% were contaminated with Escherichia coli whereas 42% were contaminated with Coagulase positive Staphylococcus and 36% were Salmonella species followed by 20%, 14% and 10% were contaminated with Enterobacter species, Coagulase negative Staphylococcus and Bacillus species respectively. A total of 174 bacteria were isolated and identified from raw chicken meat samples inspected of which 29.89% were Escherichia coli, 24.14% were Coagulase positive Staphylococcus, 20.69% were Salmonella species, 11.49% were Enterobacter species, 8.05% were Coagulase negative Staphylococcus and 5.75% were Bacillus species. The antimicrobial sensitivity tests showed that 96.15% of Escherichia coli (50 out of 52), 95.24% of Coagulase positive Staphylococcus (40 out of 42) and 86.11% of Salmonella (31 out of 36) isolates displayed multidrug resistance phenotypes (resistant to more than two antimicrobial agents). All most all the isolates of E. coli, coagulase positive Staphylococcus and Salmonella were more resistant to tetracycline, amoxicillin, ampicillin and streptomycin whereas less resistant to Ceftriaxone and Cefotaxime. The resistance patterns against azithromycin, ciprofloxacin, chloramphenicol, gentamycin, nalidixic acid and kanamycin were fluctuated from 25% to 71.43% among the isolates. This increasing development of multidrug resistance is alarming for the poultry industry and an increasing food safety concern for human.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 17-27